Pengembangan Media Pembelajaran Berbasis Powerpoint Interaktif Untuk Meningkatkan Pemahaman Etika Komunikasi Islami Siswa SMP - Mia Hasanah Amanah Illahi; Devita Hendriyanti; Arlino Pratama; Repaldy Ananditasyah Pratama; Moh Wahyudi Putra (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of this research is to develop learning media in the form of interactive PowerPoint and evaluate the feasibility of its use in improving students' understanding of Islamic communication ethics, especially for grade 9 students at SMPN 07 Jakarta. The method in this study uses R&D (research and development) with the utilization of the ADDIE model, the data is tested using the Aiken-V index. The underlying theory in this study highlights the importance of learning media as a tool that can enrich the teaching and learning process. PowerPoint was chosen because of its ease of use and its ability to present information in an attractive visual and verbal manner. This research ultimately developed learning media in the form of Interactive PowerPoint designed to improve students' understanding of Islamic communication ethics. Based on the results of the study, the interactive PowerPoint media was determined to be feasible to implement by achieving an average validity of 0.88888889 which means it meets high criteria, this research contributes to enriching the development of PowerPoint learning media and communication ethics materials at various levels.